2021
DOI: 10.1016/j.celrep.2021.109735
|View full text |Cite
|
Sign up to set email alerts
|

An additional NF-κB site allows HIV-1 subtype C to evade restriction by nuclear PYHIN proteins

Abstract: SUMMARY Subtype C is the most prevalent clade of human immunodeficiency virus type 1 (HIV-1) worldwide. The reasons for this are poorly understood. Here, we demonstrate that a characteristic additional third nuclear factor κB (NF-κB) binding site in the long terminal repeat (LTR) promoter allows subtype C HIV-1 strains to evade restriction by nuclear PYHIN proteins, which sequester the transcription factor Sp1. Further, other LTR alterations are responsible for rare PYHIN resistance of subtype B vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
(97 reference statements)
2
12
0
Order By: Relevance
“…IFI16 has been reported to inhibit viral pathogens including HIV-1 by a variety of mechanisms and has also been reported to play roles in innate sensing of viral pathogens [55][56][57] . Our finding that the inhibitory activity of IFI16 is not only evaded by an additional NF-B binding site in the LTR of currently dominating clade C viruses 44 but also counteracted by Nef further supports an important role of this antiviral factors. Our results obtained using otherwise isogenic TV constructs differing in nef are proof-of-concept that genetically closely related pairs HIV-1 strains differing in IFN sensitivity and/or accessory gene function will pinpoint factors involved in virus transmission and/or counteracted by Vif, Vpr, Vpu or Nef.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…IFI16 has been reported to inhibit viral pathogens including HIV-1 by a variety of mechanisms and has also been reported to play roles in innate sensing of viral pathogens [55][56][57] . Our finding that the inhibitory activity of IFI16 is not only evaded by an additional NF-B binding site in the LTR of currently dominating clade C viruses 44 but also counteracted by Nef further supports an important role of this antiviral factors. Our results obtained using otherwise isogenic TV constructs differing in nef are proof-of-concept that genetically closely related pairs HIV-1 strains differing in IFN sensitivity and/or accessory gene function will pinpoint factors involved in virus transmission and/or counteracted by Vif, Vpr, Vpu or Nef.…”
Section: Discussionsupporting
confidence: 61%
“…6f-h). This came as surprise since we have previously shown that IFI16 inhibits most subtypes of HIV-1 by sequestering the transcription factors Sp1 and that clade C viruses evade this restriction by acquisition of an additional NF-kB binding site 44,45 . Analysis of five pairs of WT and nef -defective HIV-1 strains including two primary subtype B and two clade C IMCs confirmed that the latter are less sensitive to the inhibitory effects of IFI16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6f–h ). This came as surprise since we have previously shown that IFI16 inhibits most subtypes of HIV-1 by sequestering the transcription factor Sp1 and that clade C viruses evade this restriction by acquisition of an additional NF-kB binding site 52 , 53 . Analysis of five pairs of WT and nef -defective HIV-1 strains including two primary subtype B and two clade C IMCs confirmed that the latter are less sensitive to the inhibitory effects of IFI16 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that not all pandemic HIV-1 strains are similarly susceptible to PTMA because they counteract or evade essentially all restriction factors (27). It has recently been shown that an additional nuclear factor κB (NF-κB) site allows HIV-1 subtype C to evade restriction by nuclear Pyrin and hematopoietic IFN-inducible nuclear (HIN) domain-containing (PYHIN) proteins (28), and it will be interesting to determine whether subtype C viruses have also evolved mechanisms to avoid restriction by PTMA. Together, the strength of the inhibitory effect of PTMA was similar to those observed in overexpression assays of tetherin, zinc-finger antiviral protein (ZAP), and guanylate binding protein 5 (GBP5) (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%